Level of Preference and Protein Analysis of Patin Dimsum Substituted with Red Bean Flour as Additional Food for Toddlers - Paramita, Irma Susan; Atasasih, Hesti; Rahayu, Dewi (Jurnal Ilmiah Kesehatan (JIKA), 2025)
The supplementary feeding program (PMT) is a crucial nutritional intervention aimed at improving toddlers' nutritional status and meeting their dietary needs. Patin fish, a local food commodity from Riau, has potential for development into attractive processed food, such as dim sum. This study aimed to evaluate the acceptability and protein content of patin fish dim sum with red bean flour substitution. A Completely Randomized Design (CRD) was used, comprising one control (100% patin) and three treatments with varying patin fish and red bean flour ratios: 95%:5%, 90%:10%, and 85%:15%. Sensory evaluation was conducted with 30 panelists and analyzed using the Kruskal-Wallis test, followed by the Mann-Whitney test if significant differences were found. The results showed a significant difference in color (p-value=0,002), while taste (p-value=0,445), aroma (p-value=0,694), and texture (p-value=0,341) showed no significant differences. The most preferred formulation was the control (without red bean flour). However, the formulation with 10% substitution (F2) had the highest protein content at 9.45%, equivalent to 9,45 grams per 100 grams of product. With this level of protein, the patin dim sum qualifies as a high-protein food product. This innovation highlights the potential of locally sourced, nutritious food for children and supports the success of supplementary feeding programs in regions like Riau that rely on local resources.